The Impact of Daughters’ Eating Disorders on Mothers’ Sense of Self: Contextualizing Mothering Experiences - Hoskins, Marie L.; Lam, Eugenie (Canadian Journal of Counselling and Psychotherapy, 2007)
This interpretive inquiry examines how daughters' anorexia influence the mothers' understandings of mothering and self within the greater context of societal influences. For the most part, psychological research has neglected this contextualized view by failing to include mothers' experiences located within cultural images, norms, rules, and expectations for what constitutes "good mothering." Using constructivist theory (Mahoney, 1991) and discursive psychology (Harre & Gillett, 1994), four themes characterised participants' relationship to cultural myths and discourses associated with eating disorders and mothering. Future research and counselling practice needs to contextualize and deconstruct the representations of mothers in any discussion of anorexia so that the needs of mothers and daughters can be supported.